Analisis Hubungan Antara Tingkat Keterpaparan Media dengan Tingkat Pemahaman Kesehatan Reproduksi Remaja di Provinsi Sumatera Utara - Windo Harjoin Sidabutar; Muhammad Ancha Sitorus; Widia Gustiasari (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
Adolescence is a period of transition from childhood to maturity. The media plays an important role in conveying the information about Adolescent Reproductive Health. The objective of this analyze was to find out the correlation of the media exposure with the Adolescent Reproductive Health knowledge. this study used the secondary data from the result of the 2017th KKJPN RPJMN Program Performance Indicator Survey. The data used was media exposure data and the adolescent reproductive health knowledge in North Sumatra in 2017. Data was analyzed using Chi Square Test . Based on the results of cross-analysis can be seen from 131 respondents exposed to information on KRR, 61 people (45.8%) of whom had a good level of KRR knowledge and 71 people (60%) had a low level of KRR knowledge. While of the 989 respondents who were exposed to less information on KRR, 204 people (20.6%) of them had a good level of KRR knowledge and 785 people (79.4) of whom had a lack of knowledge. The results of the chi-square test showed that the correlation number was 0,000 where this number was less than 0.05, so it was concluded that the KRR information exposured level had a significant correlation with the Adolescent KRR knowledge level in North Sumatera Province.